1996
DOI: 10.1016/0378-1097(95)00479-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of exoenzyme S expression by Pseudomonas aeruginosa

Abstract: The dissemination of Pseudomonas aeruginosa to the bloodstream increases the likelihood of developing fatal sepsis. In experimental models, the ability to disseminate is linked to expression of the exoenzyme S pathway. Genetic and biochemical analysis of the pathway has led to the identification of the two structural genes encoding exoenzyme S, exoS and exoT. A key regulator of several loci of the pathway has been identified as a DNA-binding protein with transcriptional activation properties. Preliminary evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…This observation can be reinterpreted in the light of our findings that the exsA mutant appears to be defective in type III secretion and fails also to secrete the 73, 40, and 32 kDa proteins. In addition, it has been reported that the presence of ExoT (but not ExoS) correlates with cytotoxicity (Frank et al, 1996). We failed to identify any transposon insertions into the exoT gene; this may reflect the fact that our screen was not exhaustive.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This observation can be reinterpreted in the light of our findings that the exsA mutant appears to be defective in type III secretion and fails also to secrete the 73, 40, and 32 kDa proteins. In addition, it has been reported that the presence of ExoT (but not ExoS) correlates with cytotoxicity (Frank et al, 1996). We failed to identify any transposon insertions into the exoT gene; this may reflect the fact that our screen was not exhaustive.…”
Section: Discussionmentioning
confidence: 79%
“…PA103, the parental strain, is cytotoxic when added to MDCK cells (Liu, 1966) and virulent in an animal model of the early events of acute pneumonia (Kudoh et al, 1994). It is a hypopiliated, non-flagellated strain that produces phospholipase C, alkaline protease, large amounts of exotoxin A, and ExoT but no ExoS (Goranson and Frank, 1996;Yahr et al, 1996a) or elastase (Liu, 1966). P. aeruginosa strain 388, which initially served as a non-cytotoxic control, is a non-isogenic strain that is non-cytotoxic in the MDCK model and avirulent in the animal model (our unpublished results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ExsA is a transcriptional regulatory protein that co-ordinately regulates several loci involved in the synthesis and secretion of extracellular proteins, postulated to be involved in the virulence of Pseudomonas aeruginosa (reviewed in Goranson and Frank, 1996). Loci transcriptionally activated by ExsA include regulatory (exsC, the B region and exsA), secretory (orf1, exsD /pscB-L) and structural components (exoS, exoT ) of the exoenzyme S regulon Hovey and Frank, 1995;Yahr et al, 1995;1996a,b).…”
Section: Introductionmentioning
confidence: 99%
“…the phagocytic activities of macrophages [14,15]. The translocation of ExoU, which has patatin-like phospholipase A 2 activity, is correlated with acute cytotoxicity in vitro and lung damage, sepsis, and mortality in animal models [7,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%